360 Virtual Tour for Online Tourism Promotion: A Study of Visual Indonesian Virtual Tour of Surabaya - Puspita Sari Sukardani,; Mutiah,; Vinda Maya Setianingrum,; Herma Prabayanti,; Sueb, (Technium Social Sciences Journal, 2023)
The presence of increasingly advanced technology has affected positively the advertising industry. The presence of a virtual tour as an alternative to virtual tourism, for instance, has offered a new space for the travel experience as users can feel how it is to be in a certain place without having to go to that place directly. In addition, virtual tours are able to provide an initial description of how a tourist object is reviewed before traveling and be used as a virtual promotional medium. As used as a means of digital promotion, the visual depiction in the virtual tour should comply with the rules of the elements and design concepts of the virtual tour. Using content analysis through explanatory approach, the results of visual observations of virtual tour objects in Indonesian Virtual Tour are Surabaya virtual tourism objects which are described even though they have fulfilled several elements of the design concept but still need to take a more selling point of view to the visitors in the case of their visit to be used as a means of tourism promotion.